2022
DOI: 10.1007/s10708-022-10579-7
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-school girls in India: a study of socioeconomic-spatial disparities

Abstract: Despite numerous established benefits of girls' education, globally large numbers of girls are out-of-school (OOS). This poses challenges to achieving quality education (SDG 4) and gender equality (SDG 5) by 2030. In India, there are socioeconomic and spatial disparities also. The latest National Sample Survey data provides an opportunity to explore these issues. We used the unit-level data of 117,115 children (5-17 years). Our multivariate logistic regression analysis shows that the likelihood of OOS girls i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Researchers have examined potential influences and identified significant effects of child, family, school, and community factors [21][22][23][24][25]. In addition to these specific concerns, the impact is even worse when child and family factors such as sex, caste, and religion combine with school-level factors such as attendance, pupil-teacher ratio, and school infrastructure [9,26,27]. An additional list of objects that are rarely researched is spatial factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have examined potential influences and identified significant effects of child, family, school, and community factors [21][22][23][24][25]. In addition to these specific concerns, the impact is even worse when child and family factors such as sex, caste, and religion combine with school-level factors such as attendance, pupil-teacher ratio, and school infrastructure [9,26,27]. An additional list of objects that are rarely researched is spatial factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the continuum of the retention universalization goal, research on factors influencing school dropout generally concentrates on child, family, school and community-related factors [4][5][6][7][8]. Only a few studies incorporated the regional variation in the proportion of dropout rate [9]. The use of geographic information systems in educational research, planning, and policy strategizing is a relatively recent development.…”
Section: Introductionmentioning
confidence: 99%
“…Society frames girls as responsible for household chores, such as cooking and housekeeping-related activities, thus denying them the opportunity to attend school (Choudhuri and Desai, 2020). There is a persistent viewpoint among most rural communities that education is not meant for girls but only for boys (Mitra et al, 2022). This exacerbates the problem of gender inequality in education outcomes.…”
Section: DI Erences Arising From Social Constructionsmentioning
confidence: 99%
“…For example, Humpert and Pfeifer (2013) reported that women in all age groups had low employment rates compared to men. Although there could be other factors contributing to the low employment of women, low education levels as a result of social construction of gender is one of them (Mitra et al, 2022). Mascherini et al (2016) also reported that women's participation in the labor market is still low despite the effort to create gender equality in employment.…”
Section: DI Erences Arising From Social Constructionsmentioning
confidence: 99%
“…About 139,000 are refugee children. UNICEF (Karamperidou, 2020) Studies indicate that rural adolescent girls are more disadvantaged, vulnerable and at risk of dropping out of school than those in urban areas (Mitra et al, 2022). The World Bank (2020) notes that female learners in South Sudan face multiple challenges in accessing and completing primary, secondary and higher education.…”
Section: Contextmentioning
confidence: 99%